P‐54: An Oxide‐Semiconductor‐FET‐Based Dynamic Logic Circuit for Wearable Systems. Issue 1 (29th May 2019) - Hamada, Toshiki; Takeuchi, Toshihiko; Aoki, Takeshi; Kozuma, Munehiro; Ikeda, Takayuki; Ikeda, Makoto; Yamazaki, Shunpei
Abstract : We propose a wearable system using oxide semiconductor (OS) transistors, which enables reduced static power of a dynamic logic device utilizing OS transistors and resulting longer continuous use of a wearable device. We fabricated a wearable‐watch‐oriented device. The results indicated that the static power could be reduced by 51%.